Alpha-cyclodextrin as a new functional ingredient in low-fat chicken frankfurter - Henck, J. M.M.; Bis-Souza, C. V. [UNESP]; Pollonio, M. A.R.; Lorenzo, J. M.; Barretto, A. C.S. [UNESP] (Taylor & Francis, 2019)
1. The current consumer preference for healthier meat products is associated with less additives in manufacturing (so-called ‘clean-label’) or the addition of non-meat ingredients with functional properties, recognised as improving specific technological properties in meat products. 2. This study evaluated the effect of the addition of alpha-cyclodextrin and wheat fibre to low-fat chicken frankfurters containing 35% mechanically deboned chicken meat on the technological and sensorial properties during refrigerated storage. 3. The results showed that the addition of dietary fibres (alpha-cyclodextrin and wheat fibre) in low-fat chicken frankfurters improved emulsion stability, hardness, chewiness and reduced cohesiveness. 4. Alpha-cyclodextrin helped the retention of fat globules in the microstructure and affected colour in the sensorial evaluation. 5. The use of alpha-cyclodextrin, in combination with wheat fibre, as a new ingredient to substitute fat in emulsified meat products containing mechanically deboned chicken, improved emulsion stability and texture. 6. Alpha-cyclodextrin and wheat fibre were effective in contributing to fat reduction without affecting the sensory properties of the product.
Keywords: Dietary fibre; emulsion stability; meat products; microstructure; sensorial properties; texture